Manajemen Kegiatan Ekstrakurikuler MSQ di MTsN 1 Agam - Panggabean, Fitri; Dewi, Puti Andam (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research is motivated by several problems, namely 1). How to plan extracurricular activities Musabaqah syarhil Al-Qur'an 2). How to organize extracurricular activities Musabaqah syarhil Al-Qur'an 3). How to implement extracurricular activities Musabaqah syarhil Qur'an 4). How is supervision in extracurricular activities Musabaqah syarhil Al-Qur'an. This research aims to find out how MSQ extracurricular activities are managed at MTsN 1 Agam. This research uses a qualitative descriptive research method, which is a form of research carried out to describe or explain phenomena regarding the conditions or symptoms being faced. The informants in this research were the Principal, Deputy Head of Curriculum, MSQ Extracurricular Advisor and MSQ Members. Meanwhile, the location of this research was carried out at MTsN 1 Agam and the data collection techniques used in this research were observation, interviews and documentation. The results of the research obtained by the author regarding Management of MSQ Extracurricular Activities at MTsN 1 Agam are 1) Planning for extracurricular activities is prepared at the beginning of the new academic year, planning extracurricular activities according to the musabaqah of the Qur'an includes making work programs, selecting supervisors, organizing structures, and implementing planning according to the vision and mission. 2) Organizing extracurricular Musabaqah syarhil Al-Qur'an includes stages, organizational structure, formation of responsible persons, preparation of training schedules and formation of teams or members. 3) The Musabaqah syarhil Al-Qur'an extracurricular activities are carried out outside of learning hours according to a predetermined schedule, namely on Wednesdays when you come home from school and accompanied by the Musabaqah syarhil Al-Qur'an instructor. 4) Supervision of Musabaqah Syarhil Quran extracurricular activities includes monitoring whether the activities are in accordance with what was planned and seeing the extent of the child's development.